An empirical study of API Management and ISO/IEC SQuaRE: a practitioners’ perspective - Dos Santos, Eder (2023)
APIs have become a cornerstone in software ecosystems: organizations have been increasingly connecting software applications to share complex digital assets. However, managing APIs is non-trivial and companies have been struggling with different quality-related issues in managing their APIs. Therefore, our goal aims to understand how practitioners perceive quality characteristics related to API management functions. To achieve it, we adopted the ISO/IEC 25010 (SquaRE) standard as the reference model and conducted a structured survey with professional developers, system administrators and software functional analysts based in Rio Gallegos City, Argentina. Questions were based on main API management capabilities discussed in current literature and their relation with the ISO/IEC 25010 quality characteristics. After running an anova analysis over 136 answered topics, results show that Functional Suitability and Security were perceived as the most critical quality capabilities, which can provide a basis for future research.